2015
DOI: 10.1175/jcli-d-14-00715.1
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Storm-Track Sensitivity to Warming Increases with Model Resolution

Abstract: Mesoscale condensational heating can increase the sensitivity of modeled extratropical cyclogenesis to horizontal resolution. Here a pseudo global warming experiment is presented to investigate how this heatingenhanced sensitivity to resolution changes in a warmer and thus moister atmosphere. The Weather Research and Forecasting (WRF) Model with 120-and 20-km grid spacing is used to simulate current and future climates. It is found that the North Atlantic storm-track response to global warming is amplified at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 61 publications
4
57
2
Order By: Relevance
“…Only the IBTrACS values for the 10 simulated years (Table 1) are considered for comparison. Consistent with similar studies (e.g., Murakami et al, 2015;Roberts et al, 2015;Yamada et al, 2017), model storms are generally weaker than observed in terms of maximum 10 m wind speed; several simulated storms do, however, attain a minimum SLP of less than 900 hPa (Fig. 7).…”
Section: Strengthsupporting
confidence: 89%
See 2 more Smart Citations
“…Only the IBTrACS values for the 10 simulated years (Table 1) are considered for comparison. Consistent with similar studies (e.g., Murakami et al, 2015;Roberts et al, 2015;Yamada et al, 2017), model storms are generally weaker than observed in terms of maximum 10 m wind speed; several simulated storms do, however, attain a minimum SLP of less than 900 hPa (Fig. 7).…”
Section: Strengthsupporting
confidence: 89%
“…A limitation of PGW case studies is the inability to study the frequency of occurrence of such events. To alleviate this limitation, some investigators have conducted long-duration regional PGW simulations (e.g., Ban et al, 2014;Willison et al, 2015;Liu et al, 2017), which allow for analysis of statistical changes extending beyond the case study of a single event. All regional PGW experiments, however, are limited by the need to impose lateral boundary conditions, which reduces the dynamical freedom of the simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some recent studies have shown that model biases and uncertainties related to explosive cyclones and the storm track in CMIP models are passively affected by the large-scale environment (Nishii et al 2015;Harvey et al 2015;Seiler and Zwiers 2016), the present study suggests that the explosive cyclone biases can be a result of the interaction between explosive cyclones and the large-scale environment. In addition, the storm-track response to the SST anomalies is sensitive to the horizontal resolution of atmospheric models (Willison et al 2013(Willison et al , 2015Smirnov et al 2015). Therefore, multiresolution experiments with coordinated SST anomalies using multi-AGCMs and atmosphere-ocean coupled GCMs will contribute to better understanding the interaction among SST fronts, the storm track, and large-scale circulations in the climate system.…”
Section: Discussionmentioning
confidence: 99%
“…(6) (open circles) for extreme events over oceans and plains. The response of midlatitude storms to warming is strongly dependent on model resolution (Willison et al 2013(Willison et al , 2015. Fraction of the area in which grid-scale condensation is occurring at 500 hPa (A s ), and the mean squared moist and dry Brunt-Väisälä frequency (N 2 m and N 2 , respectively) at 500 hPa in the saturated and the unsaturated portions of a box 508 in latitude by 708 in longitude centered at the point with maximum precipitation in the composites shown in Fig.…”
Section: Discussionmentioning
confidence: 99%